Enterococcus gilvus sp. nov. and Enterococcus pallens sp. nov. Isolated from Human Clinical Specimens - Tyrrell, Gregory J. (American Society for Microbiology, 2002)
Light yellow-pigmented (strain PQ1) and yellow-pigmented (strain PQ2), gram-positive, non-spore-forming, nonmotile bacteria consisting of pairs or chains of cocci were isolated from the bile of a patient with cholecystitis (PQ1) and the peritoneal dialysate of another patient with peritonitis (PQ2). Morphologically and biochemically, the organisms phenotypically belonged to the genus Enterococcus. Whole-cell protein (WCP) analysis and sequence analysis of a segment of the 16S rRNA gene suggested that they are new species within the genus Enterococcus. PQ1 and PQ2 displayed less than 70% identities to other enterococcal species by WCP analysis. Sequence analysis showed that PQ1 shared the highest level of sequence similarity with Enterococcus raffinosus and E. malodoratus (sequence similarities of 99.8% to these two species). Sequence analysis of PQ2 showed that it had the highest degrees of sequence identity with the group I enterococci E. malodoratus (98.7%), E. raffinosus (98.6%), E. avium (98.6%), and E. pseudoavium (98.6%). PQ1 and PQ2 can be differentiated from the other Enterococcus spp. in groups II, III, IV, and V by their phenotypic characteristics: PQ1 and PQ2 produce acid from mannitol and sorbose and do not hydrolyze arginine, placing them in group I. The yellow pigmentation differentiates these strains from the other group I enterococci. PQ1 and PQ2 can be differentiated from each other since PQ1 does not produce acid from arabinose, whereas PQ2 does. Also, PQ1 is Enterococcus Accuprobe assay positive and pyrrolidonyl-β-naphthylamide hydrolysis positive, whereas PQ2 is negative by these assays. The name Enterococcus gilvus sp. nov. is proposed for strain PQ1, and the name Enterococcus pallens sp. nov. is proposed for strain PQ2. Type strains have been deposited in culture collections as E. gilvus ATCC BAA-350 (CCUG 45553) and E. pallens ATCC BAA-351 (CCUG 45554).